2018
DOI: 10.1080/19490976.2018.1547612
|View full text |Cite
|
Sign up to set email alerts
|

A novel probiotic, Lactobacillus johnsonii 456, resists acid and can persist in the human gut beyond the initial ingestion period

Abstract: Probiotics are considered to have multiple beneficial effects on the human gastrointestinal tract, including immunomodulation, pathogen inhibition, and improved host nutrient metabolism. However, extensive characterization of these properties is needed to define suitable clinical applications for probiotic candidates. Lactobacillus johnsonii 456 (LBJ 456) was previously demonstrated to have anti-inflammatory and anti-genotoxic effects in a mouse model. Here, we characterize its resistance to gastric and bile a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 108 publications
4
41
0
Order By: Relevance
“…Evidence-based study has shown its probiotic attribute, in particular the inhibition of pathogenic Helicobacter pylori adhesion-and its subsequent activity in the human intestine-therefore reducing gastritis symptoms [46]. Aside from that, L. johnsonii has potential as marketable probiotic substance due to its great resistance towards gastric acid in stomach [47]. This bacterial species appeared to be abundant in the honey of Heterotrigona erythrogastra species (9.52%) ( Table S2).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence-based study has shown its probiotic attribute, in particular the inhibition of pathogenic Helicobacter pylori adhesion-and its subsequent activity in the human intestine-therefore reducing gastritis symptoms [46]. Aside from that, L. johnsonii has potential as marketable probiotic substance due to its great resistance towards gastric acid in stomach [47]. This bacterial species appeared to be abundant in the honey of Heterotrigona erythrogastra species (9.52%) ( Table S2).…”
Section: Discussionmentioning
confidence: 99%
“…Discrepancies associated with the treatment may be related to species 100 -and strain 101 -specific probiotic traits, resulting in differential clinical efficacy between trials comparing various probiotic microorganisms; 102 in the case of commercially available products, the batch-to-batch variation might result in different outcomes. 103 Host factors that might affect probiotics colonization and/or efficacy include diet, 104 age, 105,106 antibiotics exposure, 107,108 underlying medical conditions, 109,110 and baseline microbiome composition [111][112][113] and function. 114,115 Methodological advances in next-generation sequencing, metabolomics, and gnotobiotics, now enable a better understanding of concepts such as colonization resistance or permissiveness to exogenous microorganisms, biogeographical diversity, inter-individual variability in microbiome configuration, and how these may affect the response to therapies.…”
Section: Circumventing Old Obstacles With New Technologymentioning
confidence: 99%
“…118 Competitive exclusion of pathogens from the gut mucosa and their displacement has been suggested to be among the antagonistic mechanisms of probiotics. 112,[119][120][121][122] A beneficial effect of probiotic microorganisms on intestinal barrier integrity may also require interaction with the epithelium: Binding of L. casei GG to specific receptors on enterocytes is required to upregulate MUC2, 123 and adhesion of Lactobacillus strains to epithelial cells enhances production of MUC3. 124 However, whether such probiotics mucosal colonization universally exists remained debated.…”
Section: The Colonization Debatementioning
confidence: 99%
See 1 more Smart Citation
“…Relative abundance of L. johnsonii ranged from 34-53% and depended on acidi cation and Ca level (Table S12). Hence, treatments probably in uenced the contribution of L. johnsonii to P utilization and affected other traits of L. johnsonii; probiotic characteristics are assigned to L. johnsonii, such as reduced adhesion to the epithelial cells and inhibited growth of pathogenic microorganisms in humans [16], and they are further known to positively in uence measures related to the immune system of broilers [17]. Relative abundance of OTUs assigned to strains of L. reuteri summed up to a range of 6-26%.…”
Section: Cropmentioning
confidence: 99%